2000
DOI: 10.1021/jf991079y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis, Grease Permeation, and Water Barrier Properties of Zein Isolate Coated Paper

Abstract: An inexpensive zein-lipid mixture was isolated from yellow dent, dry-milled corn. Grease permeation through zein isolate applied to brown Kraft paper was found to be independent of loading levels at zein isolate levels above 30 mg/16 in.(2). The data shows that water vapor transmission rates depended on the amount of coating applied. Triacylglycerols were the most abundant lipid in milled corn but were absent in the zein isolate (perhaps due to hydrolysis by lipases). Zein from the paper was hydrolyzed enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Although grease resistance was lowest for the lowest coating weight, there was no significant difference in grease resistance between 7.9 and 15.8 g/m 2 . Other authors [235] observed, that grease permeation through zein isolate levels above a specific value is independent on coating weight. However, water vapor permeation correlated with coating thickness.…”
Section: Barrier Propertiesmentioning
confidence: 89%
See 3 more Smart Citations
“…Although grease resistance was lowest for the lowest coating weight, there was no significant difference in grease resistance between 7.9 and 15.8 g/m 2 . Other authors [235] observed, that grease permeation through zein isolate levels above a specific value is independent on coating weight. However, water vapor permeation correlated with coating thickness.…”
Section: Barrier Propertiesmentioning
confidence: 89%
“…Parris et al [235] evaluated the hydrolysis of zein by R-chymotrypsin, pancreatin 8ˆand pancreatin 1ˆ. After 10 and 30 min, no additional growth in the hydrolysate peak arose for R-chymotrypsin and pancreatin 8ˆ.…”
Section: End Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…The coated paper with corn zein can be used as wrapping paper for sandwich packaging, having grease barrier properties as effective as PE coated papers [72]. By spray coating the corn zein on Kraft paper, an improvement in grease resistance and WVP properties was seen along with the possibility of easy recycling and repulping through enzymatic hydrolysis in comparison with wax-treated papers [31].…”
Section: Corn Zeinmentioning
confidence: 99%